Effect of Planting Distance and Dosage of Chicken Manure on Production and Botanical Composition of Taiwan Elephant Grass (Pennisetum purpureum cv. Taiwan) at Different Cutting Phases - I Dewa Nyoman Sudita; Ni Ketut Mardewi; Marselina Ngongo (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2021)
Availability of forage fodder both in quality and quantity is an important factor in determining the success of the ruminant livestock business. The purpose of this study was to determine the effect of plant spacing and fertilizer dosage on the production of Taiwan Elephant Grass (Pennisetum purpureum cv. Taiwan) at different cuts. The field research was conducted using a Randomized Block Design (RAK) with a 3 x 4 factorial pattern, where three treatments were plant spacing (Factor A), and four treatments were dosed with fertilizer (Factor B). Each treatment combination was repeated three times so that there were 36 plots of treatment combinations. (Factor A) which consists of 3 types of spacing, namely (J1 ) 30 x 50 cm, (J2 ) 40 x 50 cm, (J3 ) 50 x 50 cm and 4 doses of fertilizer treatment (Factor B) which consists of 4 doses of fertilizer namely without fertilizer (D0), 10 tons//ha (D1), 20 tons/ha (D2), 30 tons/ha (D3). The variables measured were total plant production, botanical composition, and air dry weight (DW). Based on the study results, the spacing treatment had a significant effect (P<0.05) on the total production of Taiwan Elephant Grass stems at the first cutting. In contrast, the total plant weight, % stem, % leaf, air-dry weight (DW) had no significant effect (P> 0.05) on all observed variables. All the variables observed at the second and third cuts were not significantly different (P>0.05), but the total crop production at the third cut was higher than the second cut. The type of fertilizer had no significant effect (P>0.05) on all observed variables such as total plant weight, % stem, % leaf, total stem weight, total leaf weight.